1998
DOI: 10.1074/jbc.273.52.34687
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Domain of RGS4 Confers Receptor-selective Inhibition of G Protein Signaling

Abstract: Regulators of heterotrimeric G protein signaling (RGS) proteins are GTPase-activating proteins (GAPs) that accelerate GTP hydrolysis by G q and G i ␣ subunits, thus attenuating signaling. Mechanisms that provide more precise regulatory specificity have been elusive. We report here that an N-terminal domain of RGS4 discriminated among receptor signaling complexes coupled via G q . Accordingly, deletion of the N-terminal domain of RGS4 eliminated receptor selectivity and reduced potency by 10 4 -fold. Receptor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 231 publications
(220 citation statements)
references
References 21 publications
11
205
1
3
Order By: Relevance
“…These results further confirmed that osteoclastogenesis was impaired in the CD11b;Rgs12 fl/fl group. Accumulating studies showed that Rgs proteins have a critical role in regulating Ca 2+ oscillations in various cells, including pancreatic acinar cells and T lymphocytes, [30][31][32][33] and that Ca 2+ oscillations and NFAT2 activation are essential for RANKL-induced OC differentiation. 13 Thus we hypothesized that Rgs12 is a specific regulator of Ca 2+ oscillations in response to RANKL during OC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…These results further confirmed that osteoclastogenesis was impaired in the CD11b;Rgs12 fl/fl group. Accumulating studies showed that Rgs proteins have a critical role in regulating Ca 2+ oscillations in various cells, including pancreatic acinar cells and T lymphocytes, [30][31][32][33] and that Ca 2+ oscillations and NFAT2 activation are essential for RANKL-induced OC differentiation. 13 Thus we hypothesized that Rgs12 is a specific regulator of Ca 2+ oscillations in response to RANKL during OC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Since most of the RGS residues in direct contact with G ␣ are well conserved across the entire family, these residues are unlikely to determine RGS-G protein specificity alone. Rather, additional regulatory proteins, such as effectors (11), G␤ proteins (9,(35)(36)(37)(38), or G proteincoupled receptors (7,39) may be involved. Since five classspecific residues (r77, r117, r121, r122, r124, and r125) cluster above the RGS-G ␣ interface to form an active site common to all members of the family, a reasonable hypothesis is that this is the binding site for additional proteins that mediate specificity (Fig.…”
Section: Discussion Evolutionary Analysis Can Provide Insight Into Rgmentioning
confidence: 99%
“…Growing evidence suggests these domains do play an important role in the function of the RGS domain itself. For example, the amino terminus of RGS4 has been shown to provide agonist-dependent regulation of PLCmediated Ca 2ϩ release in rat pancreatic acinar cells (39), and the amino terminus of GAIP provides specificity for the G omediated desensitization of presynaptic Ca 2ϩ channels in chick sensory neurons (40). Furthermore, truncation of the amino terminus from RGS16 (41) results in improper cellular localization and a corresponding loss of intracellular GAP activity.…”
Section: Discussion Evolutionary Analysis Can Provide Insight Into Rgmentioning
confidence: 99%
“…The RGS proteins are Gα GTPase activating proteins (GAP) composed of a highly conserved RGS box of about 110 amino acids and divergent C-and N-termini. The GAP activity of the RGS proteins is mediated by the RGS box [39], whereas the N-terminus domain mediates membrane targeting and confers receptor recognition [40]. Receptor recognition is mediated by binding of the Nterminus of RGS proteins and the third intracellular loop of GPCRs to the scaffolding protein spinophilin [41].…”
Section: Homer 2 and Rgs Proteins Gap Activitymentioning
confidence: 99%